30 godina nakon 9.11.1989. / 30 Years after 11th of September 1989.: Koliko Njemački bi trebala imati Evropa / How many Germanies should be in Europe - H. Bajrektarević, Anis (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
An earlier version of the text has been published in over twenty countries on four contitents so far. The English original: 30 Year after the Berlin Wall Downing: The End of Coherent Universalism? Translated by Selma Aljović M.Sc. (Rev. A.B.).